Long-Term Pharmacological and Psychosocial Outcomes of Adolescent-Onset Epilepsy: A Single-Center Experience - Hyun-Jin Kim; Han Na Jang; Hyun-Ji Ahn; Mi-Sun Yum; Tae-Sung Ko (Korean Child Neurology Society, 2023)
Purpose Despite the high incidence of epilepsy during adolescence, little attention has been paid to the outcomes and prognosis of adolescent-onset epilepsy. The aim of this study was to investigate the long-term pharmacological and psychosocial outcomes of adolescent-onset epilepsy. Methods From 1993 to 2019, the electronic medical records of adolescent-onset epilepsy patients were retrieved from Asan Medical Center Children's Hospital. Seizure outcomes were evaluated based on the seizure-free period at last contact. Possible predictors of remission, relapse, and intractability were investigated. Neuropsychiatric comorbidities, socioeconomic status, and transition outcomes were also assessed. Results In total, 137 patients were enrolled in this study. The median age at diagnosis of epilepsy was 14 years and the mean duration of therapy was 13.0 years. During follow-up, 93 patients (67.9%) achieved terminal remission, of which 27 cases (19.7%) resolved. Relapse after withdrawal of medication occurred in 74 patients (54.0%), and the presence of electroencephalographic abnormalities (odds ratio [OR], 8.23; 95% confidence interval [CI], 1.39 to 48.87; P=0.020), poor adherence (OR, 4.84; 95% CI, 2.13 to 11.02; P=0.000), and history of febrile seizures (OR, 4.10; 95% CI, 1.21 to 13.93; P=0.024) were risk factors for relapse. Neurodevelopmental and psychological comorbidities were documented in 17 (12.4%) and 12 (8.8%) patients, respectively. Thirty-six (26.3%) patients transferred to adult clinics, at a mean age of 21.9 years. Conclusion This study showed overall favorable seizure outcomes with a high rate of remission, but with frequent relapse after withdrawal.